Nucleic acid oxidation: an early feature of Alzheimer's disease. (21st October 2013) - Bradley‐Whitman, Melissa A.; Timmons, Michael D.; Beckett, Tina L.; Murphy, Michael P.; Lynn, Bert C.; Lovell, Mark A.
Abstract Studies of oxidative damage during the progression of Alzheimer's disease (AD) suggest its central role in disease pathogenesis. To investigate levels of nucleic acid oxidation in both early and late stages of AD, levels of multiple base adducts were quantified in nuclear and mitochondrial DNA from the superior and middle temporal gyri (SMTG), inferior parietal lobule (IPL), and cerebellum (CER) of age‐matched normal control subjects, subjects with mild cognitive impairment, preclinical AD, late‐stage AD, and non‐AD neurological disorders (diseased control; DC) using gas chromatography/mass spectrometry. Median levels of multiple DNA adducts in nuclear and mitochondrial DNA were significantly (p ≤ 0.05) elevated in the SMTG, IPL, and CER in multiple stages of AD and in DC subjects. Elevated levels of fapyguanine and fapyadenine in mitochondrial DNA suggest a hypoxic environment early in the progression of AD and in DC subjects. Overall, these data suggest that oxidative damage is an early event not only in the pathogenesis of AD but is also present in neurodegenerative diseases in general. <boxed-text content-type="graphic" id="jnc12444-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Levels of oxidized nucleic acids in nDNA and mtDNA were found to be significantly elevated in mild cognitive impairment (MCI), preclinical Alzheimer's disease (PCAD), late‐stage AD (LAD), and a pooled diseased control group (DC) of frontotemporal dementia (FTD) and dementia with Lewy bodies (DLB) subjects compared to normal control (NC) subjects. Nucleic acid oxidation peaked early in disease progression and remained elevated. The study suggests nucleic acid oxidation is a general event in neurodegeneration.